ANÁLISIS FINANCIERO EN “CHIQUILLADAS JUNTOS DESDE EL PRIMER PASO” DE LA CIUDAD DE LOJA, PERÍODOS 2015-2016 - Quevedo Vega, Carolina Elizabeth (2019)
The thesis work named financial analysis in “CHIQUILLADAS JUNTOS DESDE EL PRIMER PASO” DE LA CIUDAD DE LOJA, PERÍODOS 2015 – 2016; It was carried out to fulfill the prerequisite to choose the degree of engineer in accounting and auditing, C.P.A, Stately of Loja University, adjusting this form to the academic regime regulation. His development allowed to comply with the general objective which was raised for the thesis work, which focused on performing a financial analysis in "Chiquilladas together from the first step" of the city of Loja, 2015-2016 period, was developed with the order to understand and analyze the economic and financial situation of the company, allowing the owner to take decisions for the benefit of the same. So we proceeded to perform vertical analysis, to determine the degree of participation of each of the accounts of the financial statements in relation to the Group and subgroup they belong to, getting to know the structure, economic and financial; horizontal analysis was then performed to establish the increases and decreases that have had accounts from a period to another as a result of the operations carried out in the years 2015 and 2016. Subsequently, indicating that the company has sufficient liquidity to cover debts in the short term, within the activity indicators showed that the rotation of the goods is favorable, the recovery of accounts receivable is satisfactory 6 as the time in which payments are made to suppliers, applying debt indicators met that the company is not in the capacity of cover its liabilities and take on new debts, by using indicators of profitability was the generation of a low level of performance that do not compensate for the investment made. So also through the Dupont system applied the return on assets and heritage, to reveal the results that was not generated profits and asset rotation improved but were not obtained benefits for the company, in the same way with respect to the capital as an unfavorable outcome since it does not compensate for the investment of the owner and the preparation of the financial report allowed to meet the economic and financial situation of the company through the financial information collected during the analysis process. The final conclusion of the work is that the company since its inception has not made the implementation of financial indicators, so it didn't allow him to know their financial health during these periods studied, in such a way that you can avoid possible alterations to they affect the development and growth of the company, which merits the manager-owner recommend the application of indicators allowing you to measure liquidity, activity, indebtedness and profitability, so that you may take measures necessary, corrective and time, in order to avoid any changes, which may occur in the company.